Early extracellular matrix changes are associated with later development of bronchiolitis obliterans syndrome after lung transplantation. Issue 1 (12th April 2017) - Müller, Catharina; Andersson-Sjöland, Annika; Schultz, Hans Henrik; Eriksson, Leif T; Andersen, Claus B; Iversen, Martin; Westergren-Thorsson, Gunilla
Abstract : Background: Chronic lung allograft dysfunction in the form of bronchiolitis obliterans syndrome (BOS) is the main cause of death beyond 1-year post-lung transplantation. The disease-initiating triggers as well as the molecular changes leading to fibrotic alterations in the transplanted lung are largely unknown. The aim of this study was to identify potential early changes in the extracellular matrix (ECM) in different compartments of the transplanted lung prior to the development of BOS. Methods: Transbronchial biopsies from a cohort of 58 lung transplantation patients at the Copenhagen University hospital between 2005 and 2006, with or without development of BOS in a 5-year follow-up, were obtained 3 and 12 months after transplantation. Biopsies were assessed for total collagen, collagen type IV and biglycan in the alveolar and small airway compartments using Masson's Trichrome staining and immunohistochemistry. Results: A time-specific and compartment-specific pattern of ECM changes was detected. Alveolar total collagen (p=0.0190) and small airway biglycan (p=0.0199) increased between 3 and 12 months after transplantation in patients developing BOS, while collagen type IV (p=0.0124) increased in patients without BOS. Patients with early-onset BOS mirrored this increase. Patients developing grade 3 BOS showed distinct ECM changes already at 3 months. Patients with BOS with treated acute rejections displayed reduced alveolar total collagen (p=0.0501) and small airway biglycan (p=0.0485) at 3 months. Conclusions: Patients with future BOS displayed distinct ECM changes compared with patients without BOS. Our data indicate an involvement of alveolar and small airway compartments in post-transplantation changes in the development of BOS.